IMCRYPTO: An In-Memory Computing Fabric for AES Encryption and Decryption - Reis, Dayane; Geng, Haoran; Niemier, Michael; Hu, Xiaobo Sharon (IEEE transactions on very large scale integration (VLSI) systems, 2022)
This article proposes IMCRYPTO, an in-memory computing (IMC) fabric for accelerating advanced encryption standard (AES) encryption and decryption. IMCRYPTO employs a unified structure to implement encryption and decryption in a single-hardware architecture with combined (Inv)SubBytes and (Inv)MixColumns steps. Because of this step combination and the high parallelism achieved by multiple units of random access memory (RAM) and random access/content addressable memory (RA/CAM) arrays, IMCRYPTO achieves high-throughput encryption and decryption without sacrificing area and power consumption. In addition, due to the integration of an RISC-V core, IMCRYPTO offers programmability and flexibility. IMCRYPTO improves the throughput per area by a minimum (maximum) of 3.3× ( 223.1× ) compared to previous ASICs/IMC architectures for AES-128 encryption. Projections show added benefit from emerging technologies of up to 5.3× to the area-delay-power product of IMCRYPTO.